Distribution of and the taxonomic keys to the species in the genus Daptonema Cobb, 1920 in Vietnam - Tu, Nguyen Dinh; Thanh, Nguyen Vu (Academia Journal of Biology, 2019)
Up to now, 22 nematodes species have been recognized in the genus Daptonema Cobb, 1920 from mangrove, river and estuary ecosystems in Vietnam, with 18 species described as new species and 4 others recognized for science. Three species, D. dihystera Gagarin and Nguyen Vu Thanh, 2005, D. salvum Gagarin, Nguyеn Vu Thanh & Nguyen Thi Thu, 2005 and D. rigidum Gagarin, Nguyеn Vu Thanh & Ngudyen Thi Thu, 2005 were found in fresh water, while other species were distributed in the mangrove forest, estuaries and seagrass ecosystem. The distribution and taxonomic keys to the species in the genus Daptonema Cobb, 1920 in Vietnam have been provided.